2018
DOI: 10.3390/pharmaceutics10040232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β-Sitosterol Loaded PLGA and PEG-PLA Nanoparticles for Effective Treatment of Breast Cancer: Preparation, Physicochemical Characterization, and Antitumor Activity

Abstract: β-Sitosterol (β-Sit) is a dietary phytosterol with demonstrated anticancer activity against a panel of cancers, but its poor solubility in water limits its bioavailability and therapeutic efficacy. In this study, poly(lactide-co-glycolic acid) (PLGA) and block copolymers of poly(ethylene glycol)-block-poly(lactic acid) (PEG-PLA) were used to encapsulate β-Sit into nanoparticles with the aim of enhancing its in vitro anticancer activity. β-Sitosterol-loaded PLGA and PEG-PLA nanoparticles (β-Sit-PLGA and β-Sit-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…With regard to research work carried out in literature to boost β-sitosterol biopharmaceutical efficiency using nanocarriers, the specific formulation such as PLGA-loaded β-sitosterol nanoparticles (Andima et al., 2018 ). While these discuss formulation exhibited a definite improvement in the drug's biopharmaceutical attributes, the current investigation was undertaken to discuss the significant finding of β-sitosterol-SLNs systematically optimized to enhance the effectiveness of drug therapy against CFA-induced arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to research work carried out in literature to boost β-sitosterol biopharmaceutical efficiency using nanocarriers, the specific formulation such as PLGA-loaded β-sitosterol nanoparticles (Andima et al., 2018 ). While these discuss formulation exhibited a definite improvement in the drug's biopharmaceutical attributes, the current investigation was undertaken to discuss the significant finding of β-sitosterol-SLNs systematically optimized to enhance the effectiveness of drug therapy against CFA-induced arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA is one of the most extensively used biodegradable polymers because its hydrolysis leads to endogenous and easily metabolized monomers of lactic acid and glycolic acid [11]. Recent publications suggest that PLGA-NPs functionalized with (i) ß-Sitosterol, a natural phytosterol, (ii) resveratrol, a natural polyphenol, and (iii) tea polyphenols of theaflavin and epigallocatechin-3-gallate [12,13,14] might be potential candidates for cancer treatment. Many studies have revealed that encapsulation of PLGA nanoparticles improves the biocompatibility, tunable mechanical property, and controllable degradation of several chemotherapeutic drugs including paclitaxel, tamoxifen, and anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…The loading of therapeutic drugs into PLA and PLGA synthetic NPs provides many advantages, such as drug protection from enzymatic degradation and promotion of a sustained release. Recent reports demonstrate that these NPs complexed to anticancer drugs can be used for efficient drug delivery [ 75 ] and for reduced nanotoxicity [ 76 ].…”
Section: Nanoparticles For Cancer Treatmentmentioning
confidence: 99%